Effect of Cr content on mechanical and electrical properties of Ni-Cr thin films - Danisman, M.; Cansever, N. (ELSEVIER SCIENCE SA, 2010)
NiCr has been a popular choice for strain gage and electrical resistance application in various fields of engineering and science. Therefore, the phases at this binary system have been thoroughly investigated in the last decade. For Ni-Cr thin film production, sputtering from alloy targets is mostly discussed as a deposition method. However, Cr content in Ni-Cr alloy has major influence on different properties of the NiCr thin films. In order to investigate the effect of Cr content in Ni-Cr system, Ni over Cr thin films with a total thickness of 500 nm was deposited on glass substrates with different Cr/Ni thickness ratios as 0.1, 0.25 and 0.6. After deposition, thin films were annealed at 600 degrees C for 180s in a Rapid Thermal Process (RTP) system to investigate the effect of different Cr contents on phase formation. The phase formations and lattice parameters were analyzed with low glancing angle X-ray Diffraction (XRD) and the Cr content in the thermally treated thin films was calculated with Energy Dispersive Spectrometry (EDS). Also, film composition along depth was also calculated by EDS analysis from the cross-section view of the annealed samples. Field Emission Scanning Electron Microscope (FESEM) images were taken from the cross-section view of the samples in order to observe the final film thicknesses and structures. Sheet resistance of each sample was measured with linear four point probe technique and resistivity of each phase was calculated. Furthermore, nanohardness and Young's Modulus of each sample was calculated by using nanoindentation method. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ni-Cr phases; Sputtering; RTP; XRD; SURFACE-COMPOSITION; TEMPERATURE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering